Sistem Pelayanan Publik Sebagai Peningkatan Kepuasan Masyarakat - Rani Nurul Laili Herzegovina; Syauqi Taufiqurrohman (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2022)
Public Service is action or activity that can be offered by one party to another, which is basically intangible and does not result in the ownership of anything. One of the government offices whose activities provide public services to the community is the district office. The research method is a qualitative research method which is arranged descriptively. The location of this research is in the District Office of Padang, Lumajang Regency. The subjects of this research are the staff in the service department. The types of research instruments are observation and interviews, and the latter is in the form of documentation during the observation and interviews. The results of the study show that the services provided are related with population administration and other services related with government at the sub-district level. The systems, mechanisms and procedures provided at the sub-district office are very adequate and good, they are given to all service users. The facilities and infrastructure provided at the sub-district office are very adequate and good, this is provided for service users in order to increase community satisfaction in the quality service.